Bridging the Gap or Widening the Divide? The Role of Technology in Global Economic Inequality - Eshehri, Abdulrhman; Alsoaery, Abdulrhman (Archives of Business Research, 2023)
This article explores the relationship between technological advancements, transnational capitalism, and the growing divide in global economic inequality. It analyzes how developed nations’ dominance in technology research and innovation has contributed to the disproportionate distribution of wealth, productivity, and economic development. By examining data such as G7 countries’ investments in research and development, accounting for over 88% of global expenditure, and their holding of over 90% of patents filed in 2014, the article highlights the intricate links between multinational corporations, technological diffusion, and global inequality. The findings reveal that the concentration of technological advancements in a few developed countries not only fuels global capitalism but also exacerbates the economic disparities between rich and poor nations. The article calls for a more equitable approach to technological development and diffusion to bridge this widening gap.